Mendel 2015 Recent Advances in Soft Computing - Matoušek, Radek (Springer, 2015)
This book is a collection of selected accepted papers of Mendel conference that has been held in Brno, Czech Republic in June 2015. The book contents three chapters which represent recent advances in soft computing including intelligent image processing and bio-inspired robotics.: Chapter 1: Evolutionary Computing, and Swarm intelligence, Chapter 2: Neural Networks, Self-organization, and Machine Learning, and Chapter3: Intelligent Image Processing, and Bio-inspired Robotics. The Mendel conference was established in 1995, and it carries the name of the scientist and Augustinian priest Gregor J. Mendel who discovered the famous Laws of Heredity. In 2015 we are commemorating 150 years since Mendel's lectures, which he presented in Brno on February and March 1865. The main aim of the conference was to create a periodical possibility for students, academics and researchers to exchange their ideas and novel research methods.